SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN TOMAT MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Iqbal Wilson; Elfi Fauziah (CV. Multi Kreasi Media, 2024)
The expert system for diagnosing tomato plant diseases using the web-based forward chaining method in West Lampung Liwa was created to identify the symptoms of tomato diseases and solutions for handling tomato plants, providing solutions to farmers for dealing with tomato plant diseases, to implement the forward chaining method in the diagnosis process diseases that exist in tomato plants based on predetermined rules. An expert system for diagnosing tomato plant diseases using a website-based forward chaining method is designed using the PHP programming language and a MySQL database which in the final stage can function to make data processing easier, for the implementation stage it uses UML (Unified Modeling Language) which can analyze input and data output. The forward chaining method is drawing conclusions based on existing facts leading to that conclusion using the IF part of the IF-THEN rule. To ensure the system runs well, two stages of testing are carried out, namely white box and black box testing in the process of managing symptom data, managing rice disease data and testing to display the results of disease diagnosis reports on tomato plants.